Respostas

2013-05-28T20:11:21-03:00

(a-2b)[a(b-3)+b(1-a)]=
(a-2b)[ab-3a+b-ab]=
(a-2b)(-3a+b)=
-3a²+ab+6ab-2b²=
-3a²+7ab-2b²

1 5 1
2013-05-28T20:43:10-03:00

ax²+b(x+1)²+c(x+2)² = (x+3)² 
ax² +b(x² + 2x + 1) + c(x² + 4x + 4) = x² + 6x + 9
ax² +bx² + 2bx + b + cx² + 4cx + 4c = x² + 6x + 9
(a + b + c)x² + (2b + 4c)x + b + 4c = x² + 6x + 9
Pela indentidade de polinomios temos que
a + b + c = 1
2b + 4c = 6 ( multiplicando por -1 e somando com a de baixo )
b + 4c = 9
-2b + b -4c + 4c = -6 + 9
-b = 3 
b = -3 -> c = 3 -> a = 1
portanto a - b + c = 1 -(-3) + 3 = 1 + 3 + 3 = 7

 

2 4 2